STRATEGI PRODUKSI DAN KREATIF MNC CHANNELS DALAM MENGEMAS PROGRAM LOKAL (STUDI KASUS ACARA JAN ENAK TENAN) - Aditya Rangga Prayoga; M Jamiluddin Ritonga (Jurnal Komunikasi, 2026)
This study examines the production and creative strategies implemented by MNC Channels in packaging the local television program Jan Enak Tenan amid digital media competition in Indonesia. As a culinary program highlighting Javanese culture, it integrates entertainment, education, and cultural representation. Using an interpretive paradigm and a qualitative case study approach, data were collected through in-depth interviews, observation, and documentation. Analysis followed the interactive model of Miles and Huberman, supported by source triangulation. Findings show that production strategies are systematically applied across pre-production, production, and post-production, emphasizing audience research, technical planning, on-site flexibility, and editorial quality control. Creative strategies include trend-based idea development from social media, culinary storytelling, exploration of Javanese cultural identity, strong host characterization, and engaging visuals. From Stuart Hall’s encoding–decoding perspective, producers intentionally encode cultural and entertainment messages, while audiences engage in dominant and negotiated readings. The study concludes that integrating structured production management and adaptive creative strategies is essential to sustain the relevance and competitiveness of local television programs in the digital era.